KERAGAAN KEDELAI NASIONAL DAN ANALISIS FARMER SHARE SERTA EFISIENSI SALURAN PEMASARAN KEDELAI DI KABUPATEN CIANJUR - CHAIRUL MUSLIM; VALERIANA DARWIS (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Soybean is one of the strategic commodities, it is constituted in terms of benefits and terms of consumption increases with the increase of population. But in terms of local production can not meet the needs of soybean, so it issued a policy to import. One reason is the lack of local soybean production soybean prices fluctuated and the price of soybeans is not attractive compared to other food commodities, while the selling price is also affected by the length of the marketing chain soybeans.